2021
DOI: 10.1093/noajnl/vdab109
|View full text |Cite
|
Sign up to set email alerts
|

Defining the molecular features of radiation-induced glioma: A systematic review and meta-analysis

Abstract: Background Cranial radiation therapy is essential in treating many pediatric cancers, especially brain tumors, however its use comes with the risk of developing second malignancies. Cranial radiation-induced gliomas (RIGs) are aggressive high-grade tumors with a dismal prognosis, for which no standard therapy exists. A definitive molecular signature for RIGs has not yet been established. We sought to address this gap by performing a systematic review and meta-analysis of the molecular feature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
15
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(17 citation statements)
references
References 100 publications
2
15
0
Order By: Relevance
“…Two patients had a hypermethylated MGMT promoter; the other 6 patients had a hypomethylated MGMT promoter. These results are consistent with those of previous reports and confirm the genetic characteristics of RIG [ 10 15 , 32 ]. Recent comprehensive molecular analyses revealed that RIGs had recurrent PDGFR amplification, loss of CDKN2A/B and absence of histone 3 and IDH1/2 mutations and also showed that their DNA methylation patterns closely resembled those of sporadic pediatric GBM RTK1 tumors [ 14 , 15 , 32 ].…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Two patients had a hypermethylated MGMT promoter; the other 6 patients had a hypomethylated MGMT promoter. These results are consistent with those of previous reports and confirm the genetic characteristics of RIG [ 10 15 , 32 ]. Recent comprehensive molecular analyses revealed that RIGs had recurrent PDGFR amplification, loss of CDKN2A/B and absence of histone 3 and IDH1/2 mutations and also showed that their DNA methylation patterns closely resembled those of sporadic pediatric GBM RTK1 tumors [ 14 , 15 , 32 ].…”
Section: Discussionsupporting
confidence: 94%
“…Recent comprehensive molecular analyses revealed that RIGs had recurrent PDGFR amplification, loss of CDKN2A/B and absence of histone 3 and IDH1/2 mutations and also showed that their DNA methylation patterns closely resembled those of sporadic pediatric GBM RTK1 tumors [ 14 , 15 , 32 ]. These observations suggest that RIGs are molecularly distinct from adult diffuse gliomas and aberrant activation of the MAPK/ERK pathway together with loss of cell cycle control facilitates the tumorigenesis of RIG [ 14 , 15 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…A mutagenic action of radiation on TP53 has been hypothesized by small series on radiation-induced tumors. For instance, TP53 mutations were reported in 58% of radiation-induced sarcomas [ 39 ], while a meta-analysis reported TP53 mutations in 14/30 radiation-induced gliomas [ 40 ]. A previous study reported a case with frameshift TP53 mutation in the CTP-BADX/NS tumor, but not in the initial CD surgeries, and the mutation was therefore suspected to be induced by radiotherapy [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to most de novo GBs in which an inciting etiology is unknown, patients with RIGs have the unique unifying factor of clear prior mutagenic agent exposure. Because of this, it has been suggested that these RIGs may share an underlying molecular signature secondary to their pathogenesis ( 8 , 10 , 11 ). Despite the emergence of the next-generation sequencing use in glioma in recent years to better understand disease biology and evaluate patient candidacy for nontraditional therapeutic options, this testing remains an inconsistent practice, and the relative rarity of RIGs has further limited widespread reporting of characteristic alterations.…”
Section: Discussionmentioning
confidence: 99%
“…It remains unclear which patients are more likely to benefit from this therapy. In this regard, while molecular testing, including genomic sequencing, has emerged in neuro-oncology as necessary testing to establish diagnosis, prognosis, and guide therapeutic options, there remains a paucity of this data for RIGs due to its low incidence albeit with emerging evidence suggestive of a “unifying molecular signature” for this disease ( 8 , 10 , 11 ). Herein, we report two cases of aggressively behaving RIGs, diagnosed as GB, IDH-wildtype, based on histologic and molecular criteria using the revised fourth edition of the World Health Organization (WHO) Classifications of CNS Tumors, with exceptional radiographic responses to radiation therapy.…”
Section: Introductionmentioning
confidence: 99%